Stability enhancement via controller optimization and impedance shaping for dual active bridge-based energy storage systems - Feng, Fan (2022)
This article proposes two impedance compensation methods to enhance the stability of the dual active bridge (DAB) converter-based energy storage systems (ESSs). First, the design of the traditional feedback controller of the DAB converter is revisited with consideration of stability of the DAB-based ESSs. The presented analysis reveals that due to the improper design of the DAB feedback controller, the magnitude of the DAB converter input impedance will be reduced, resulting in instability problems of the DAB-based ESSs. As a straightforward solution, the optimized design guideline of the DAB feedback controller is proposed, which can solve the instability issue of the DAB-based ESS without any additional passive components or active control loops. Second, a family of impedance shaping regulators (ISRs) is proposed to modify the input impedance of the DAB converter-the bus voltage-based ISR (BV-ISR) and the bus current-based ISR (BC-ISR). The design requirements of the BV-ISR and BC-ISR to solve the instability problems of DAB-based ESS are disclosed. The dynamic responses of the proposed methods are compared. Finally, the effectiveness of the optimized DAB controller and the ISRs are validated by the experimental results.